1998
DOI: 10.1207/s15374424jccp2702_1
|View full text |Cite
|
Sign up to set email alerts
|

Empirically supported psychosocial interventions for children: An overview

Abstract: Discusses issues related to the identification of psychosocial interventions for children that have demonstrated efficacy. Recent debate concerning differences between clinical trials research and clinical practice is summarized, including the tradeoff between interpretability (internal validity) and generalizability (external validity) of outcome studies. This article serves as an introduction to the special issue containing articles that have as their focus the identification of empirically supported psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
244
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(249 citation statements)
references
References 23 publications
1
244
0
4
Order By: Relevance
“…Ollendick and King (1998) presented the first review of treatments for child and adolescent phobic and anxiety disorders that used guidelines set forth by the American Psychological Association (APA) Task Force on Promotion and Dissemination of Psychological Procedures, Division of Clinical Psychology, American Psychological Association (1995) to evaluate the efficacy of a given psychological intervention. As explained by Lonigan and colleagues (Lonigan, Elbert, & Johnson, 1998) in their introduction to the special issue examining the evidence for child and adolescent psychological treatments, the mandate of the APA task force was to ''identify specific psychosocial interventions for specific problems' ' (p. 140). Given the state of the evidence base at the time of this initial review, the evidence reviewed by Ollendick and King referred primarily to specific psychological procedures: ''systematic desensitization (both imaginal and in vivo), emotive imagery, modeling, reinforced practice, verbal self-instruction, modeling, reinforced practice, verbal self-instruction, cognitive-behavioral interventions, and integrated cognitive-behavioral plus family-based procedures' ' (p. 157).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ollendick and King (1998) presented the first review of treatments for child and adolescent phobic and anxiety disorders that used guidelines set forth by the American Psychological Association (APA) Task Force on Promotion and Dissemination of Psychological Procedures, Division of Clinical Psychology, American Psychological Association (1995) to evaluate the efficacy of a given psychological intervention. As explained by Lonigan and colleagues (Lonigan, Elbert, & Johnson, 1998) in their introduction to the special issue examining the evidence for child and adolescent psychological treatments, the mandate of the APA task force was to ''identify specific psychosocial interventions for specific problems' ' (p. 140). Given the state of the evidence base at the time of this initial review, the evidence reviewed by Ollendick and King referred primarily to specific psychological procedures: ''systematic desensitization (both imaginal and in vivo), emotive imagery, modeling, reinforced practice, verbal self-instruction, modeling, reinforced practice, verbal self-instruction, cognitive-behavioral interventions, and integrated cognitive-behavioral plus family-based procedures' ' (p. 157).…”
mentioning
confidence: 99%
“…In its initial compilation of treatments that had yielded empirical support, this Task Force decided to include the criterion of a treatment manual with the understanding that manuals were necessary for the provision and teaching of specific therapeutic interventions. The requirement of treatment manuals was not applied by the Division 53 Task Force in their construction of the initial criteria to evaluate child and adolescent psychological interventions (Lonigan et al, 1998); however, this criterion was imposed in the subsequent 2008 review. Accordingly, the focus in the review shifted to that of ''group design studies, most of which evaluated a combination of therapeutic strategies or a treatment package=program (e.g., Coping Cat; ' ' (p. 106).…”
mentioning
confidence: 99%
“…A treatment approach was included only if the Task Force concluded that there was sufficient empirical evidence demonstrating its efficacy with a particular clinical population (Chambless, 1996;Chambless & Hollon, 1998). Lonigan, Elbert, and Johnson (1998) translated the division 12 criteria to the youth treatment literature. Other researchers in the child and adolescent treatment field have also produced reviews of ESTs (Burns, Hoagwood, & Mrazek, 1999;Chorpita et al, 2002).…”
mentioning
confidence: 99%
“…1 An overriding goal of intervention research is to identify evidence-based interventions: Evidence from controlled experiments suggests these interventions change constructs they were developed to change. Researchers have developed classification systems through which a given intervention can be identified as evidence-based, based on prior well-controlled experimental outcome studies examining the intervention (e.g., Lonigan, Elbert, & Johnson, 1998;Nathan & Gorman, 2002;Roth & Fonagy, 2005). Upon scrutiny, the supportive evidence raises Correspondence regarding this manuscript should be addressed to Alan E. Kazdin, Child Study Center, Yale University School of Medicine, 230 S. Frontage Road, New Haven, CT 06520-7900.…”
mentioning
confidence: 99%
“…Thus, the TFPP's criteria employ rank-ordered categorizations of interventions. Further, the categorizations are based on whether well-controlled studies exist to support the intervention, the number of such studies, and whether these studies have been conducted by more than one independent investigator or team.As mentioned previously, other efforts to delineate evidence-based interventions have been developed (e.g., Lonigan et al, 1998;Nathan & Gorman, 2002;Roth & Fonagy, 2005), and have followed the pioneering efforts of TFPP. The criteria employed across systems may differ.…”
mentioning
confidence: 99%